Application of Polyoxidonium in the Mixed Treatment of Experimental Plague Generalized Forms - T. A. Bondareva; A. Yu. Poyarkov; E. Yu. Vakhnov (Проблемы особо опасных инфекций, 2009)
Applicability of modern immunomodulator Polyoxidonium for plague treatment was investigated. Inclusion of Polyoxidonium in the therapeutic scheme increased efficiency of treatment with antibiotics of experimental generalized plague in mice challenged with Yersinia pestis strain 231, the latter being typical representative of continental variant of plague microbe. Life duration enhancement and increase of the number of survived animals challenged with plague agent were registered after prophylactic or emergency injection of Polyoxidonium against the background of treatment with antibiotic.